Fighting for peace - Abd Razak, Dzulkifli (2005)
A game plan called the ‘science of strategy’ could be used to settle all issues peacefully. AN antiwar meeting, called the Perdana Global Peace Forum, will be convened by the Perdana Leadership Foundation Centre (www.perdana.org.my) in Kuala Lumpur next week. Tun Dr Mahathir Mohamad, president of the centre, says he wants to break the cycle of violence. Many eminent speakers are scheduled to attend the forum, themed "Peace Dividend, War Profit". It is increasingly clear many leaders thrive by using war as a platform to get elected, even if they have to lie. A classical case is of course the spin on Saddam Hussein’s weapons of mass destruction and the invasion of Iraq. Some would argue that this is what politics is all about — the art of the possible, where the end justifies the means.